Vibratory stimulation in non-growing patients and its effect on the orthodontic tooth movement - Sharma, Tanushree; Gupta, Ankita; Sharma, Aseem; Vaid, Pulkit; Singh, Kamlesh (International Journal of Scientific Reports, 2021)
Background: Objectives of the study were to determine the impact of vibratory stimulation in non-growing patients on the orthodontic tooth movement rate and to differentiate the orthodontic tooth movement rate in both experimental and control sides. Methods: 30 non-growing patients were selected for a split-mouth study with fixed appliance therapy orthodontic treatment undergoing bilateral first premolar extractions in maxillary arch. Type 1 active tiebacks were used to perform single canine retraction in all the patients. Vibratory stimulation was provided for 15 minutes daily with the help of Oral-B battery powered toothbrushes of 125 Hz frequency. Measurement was taken with calibrated digital vernier caliper clinically and OPG were taken at regular time intervals using grid method for the tooth movement calculation. Results: P value obtained by statistical calculation shows non-significant results in both experimental and control sides in non-growing patients. Conclusions: Cyclic loading in non-growing patients with fixed orthodontic appliance shows no change in orthodontic tooth movement in experimental and control group.